Temporal alignment of electrocorticographic recordings for upper limb movement - Talakoub, Omid; Popovic, Milos R.; Navaro, Jessie; Hamani, Clement; Fonoff, Erich T.; Wong, Willy (Frontiers in Neuroscience, 2015)
The detection of movement-related components of the brain activity is useful in the design of brain machine interfaces. A common approach is to classify the brain activity into a number of templates or states. To find these templates, the neural responses are averaged over each movement task. For averaging to be effective, one must assume that the neural components occur at identical times over repeated trials. However, complex arm movements such as reaching and grasping are prone to cross-trial variability due to the way movements are performed. Typically initiation time, duration of movement and movement speed are variable even as a subject tries to reproduce the same task identically across trials. Therefore, movement-related neural activity will tend to occur at different times across each trial. Due to this mismatch, the averaging of neural activity will not bring into salience movement-related components. To address this problem, we present a method of alignment that accounts for the variabilities in the way the movements are conducted. In this study, arm speed was used to align neural activity. Four subjects had electrocorticographic (ECoG) electrodes implanted over their primary motor cortex and were asked to perform reaching and retrieving tasks using the upper limb contralateral to the site of electrode implantation. The arm speeds were aligned using a nonlinear transformation of the temporal axes resulting in averaged spectrograms with superior visualization of movement-related neural activity when compared to averaging without alignment.